Giant cell arteritis: is the clinical spectrum of the disease changing? - Miguel Á. González-Gay; Miguel Ortego-Jurado; Liliana Ercole; Norberto Ortego-Centeno (BMC Geriatrics, 2019)
Abstract Background Giant cell arteritis is a vasculitis of large and middle-sized arteries that affects patients aged over 50 years. It can show a typical clinical picture consisting of cranial manifestations but sometimes nonspecific symptoms and large-vessel involvement prevail. Prompt diagnosis and treatment is essential to avoid irreversible damage. Discussion There has been an increasing knowledge on the occurrence of the disease without the typical cranial symptoms and its close relationship and overlap with polymyalgia rheumatica, and this may contribute to reduce the number of underdiagnosed patients. Although temporal artery biopsy is still the gold-standard and temporal artery ultrasonography is being widely used, newer imaging techniques (FDG-PET/TAC, MRI, CT) can be of valuable help to identify giant cell arteritis, in particular in those cases with a predominance of extracranial large-vessel manifestations. Conclusions Giant cell arteritis is a more heterogeneous condition than previously thought. Awareness of all the potential clinical manifestations and judicious use of diagnostic tests may be an aid to avoid delayed detection and consequently ominous complications.